1978
DOI: 10.1177/107769907805500301
|View full text |Cite
|
Sign up to set email alerts
|

Public Support for the Press

Abstract: Political variables were most important determinantsfor press behavior.3 Yet the factors of press criticism during which' influence public support of the Watergate period. Sociologicalpress-or its inverse, public criticismare not well understood. and psychological variables of lesser consequence. Support for the US. Press,Press systems in modem societies are the products of historical forces as well as current movements within the societies they serve, historicall and func-tional2 analyses underscore. Changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Some research has identified correlates of media credibility-such as age, sex, education-in the media audience (Becker, Cobbey, and Sobowale 1978;Lewis 1981;Westley and Severin 1964). But this work is largely atheoretical.…”
Section: Audience Demographicsmentioning
confidence: 99%
“…Some research has identified correlates of media credibility-such as age, sex, education-in the media audience (Becker, Cobbey, and Sobowale 1978;Lewis 1981;Westley and Severin 1964). But this work is largely atheoretical.…”
Section: Audience Demographicsmentioning
confidence: 99%
“…Most previous studies that have examined the quality or credibility of information have been concerned with multidimensional variables, such as accuracy, trustworthiness, believability, fairness, currency, completeness, bias factors [ 3 - 7 ], and the evaluation of health-related websites [ 4 - 8 ]. Earlier studies have indicated that the most important factor an information source credibility that it can be used to make decisions about the assessment and application of information [ 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified traditional correlates of media credibility, such as sex, age, income, and education [ 8 , 17 , 18 ]. These studies performed demographic comparisons of trust in TV and newspapers.…”
Section: Introductionmentioning
confidence: 99%